Model Pengembangan Kurikulum dan Strategi Pembelajaran Berbasis Sosiologi Kritis, Kreativitas dan Mentalitas - Mustofa Kamal (Madaniyah, 2014)
Curriculum development does not only involve people who are directly related to the world of education, but also involves many parties, such as politicians, entrepreneurs, parents of students, and other elements of society. The principles that will be used in curriculum development activities are basically the rules or laws that will animate a curriculum. Learning strategies in school education must be given a foundation in advance by internalizing critical sociology, innovation, creativity, and mentality. In addition, it also changes the learning strategy that has been based on the concept of reproductive view of learning into a constructive view of learning. The stagnation of the school education curriculum begins with the replication and adoption of a curriculum that does not fit the character of students. The inclusion of creativity in the curriculum results in inhibition of the power of innovation, inspiration, and imagination while blunting intuition in the development of school education. Values ​​of mentality, such as honesty, fairness, love, and affection are still not visible in the school education curriculum. The curriculum development model based on critical sociology, creativity, and mentality must be supported by innovative learning strategies or different from previous strategies. Freedom of creation in the development of an educational curriculum makes the key to the birth of creators who are able to meet all the needs of society and the guidance of the times.